Design For Development of PAI Curriculum in Madrasah Views from Science and Technology - Neliana, Neliana; Hamzah, Syukri; Danim, Sudarwan (PPSDP International Journal of Education, 2024)
The aim of this research is to analyze the views of science and technology in curriculum development design. The research method used is the library research method with books and journals as sources of information. The results of this research are: According to a review of the basis of science and technology, the design of PAI curriculum development in madrasah for each component must include science and technology in it, including objectives, materials, methods and evaluation. Then, in including science and technology in the development of the PAI curriculum in madrasah, there are several things that must be taken into account, including: a) must be effectively and dynamically balanced with human resource development, conducting research, and developing science and technology infrastructure; b) aimed at improving the nation’s quality of life and prosperity; c) must be in harmony with religious values, socio-economic conditions and culture at a higher level of productivity and development; and d) must have the ability to solve specific problems.